Occurrence of fungi on tissues of the peat swamp palm Licuala longicalycata - Pinruan U. (2014)
The biodiversity of fungi from decaying palm material of Licuala longicalycata was studied following six field collections in May, June, September and November 2001, and February and May 2002. One-hundred and seventy-seven fungal collections were identified to species level, 153 collections to generic level, while 28 collections remained unidentified. A total of 147 species were identified, including 79 ascomycetes in 50 genera (53%), 65 anamorphic taxa in 53 genera (45%) and 3 basidiomycete species in 3 genera (2%). Nine ascomycetes and 5 anamorphic fungi were new to science. The percentage of fungi occurring in different microhabitats were as follows: dry material supported the most fungi with 40%, submerged material had 32%, while the damp material supported the least number of fungi (28%). The percentage occurrence of fungi on different tissues of L. longicalycata were: petioles 61%, trunks 24%, and leaves 15%. The most common fungi were Annulatascus velatisporus, Microthyrium sp., Phaeoisaria clematidis, Massarina bipolaris, Phruensis brunneispora, Thailiomyces setulis, and Solheimia costaspora. Species diversity on L. longicalycata was high, with little overlap with fungal communities on other palms. Factors affecting the colonization of palm material in the peat swamp are discussed.